2010
DOI: 10.1136/hrt.2010.194118
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular myocardial deformation and mechanical dyssynchrony in children with normal ventricular shortening fraction after anthracycline therapy

Abstract: Impaired left ventricular myocardial deformation and mechanical dyssynchrony may exist in children after anthracycline therapy despite having normal left ventricular shortening fractions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
107
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(119 citation statements)
references
References 33 publications
10
107
2
Order By: Relevance
“…In our study, the RS, as well as LS and CS showed significant reduction after chemotherapy, which was in concordance with some previous studies [12,16], however, discordant with others [11,17]. Ho et al [11] demonstrated that there was no significant difference in RS between the chemotherapy and control groups.…”
Section: Beforesupporting
confidence: 80%
See 2 more Smart Citations
“…In our study, the RS, as well as LS and CS showed significant reduction after chemotherapy, which was in concordance with some previous studies [12,16], however, discordant with others [11,17]. Ho et al [11] demonstrated that there was no significant difference in RS between the chemotherapy and control groups.…”
Section: Beforesupporting
confidence: 80%
“…With the advantages of angle independence, speckle tracking echocardiography, allowing comprehensive assessment of both regional and global LV myocardial deformation, may provide reliable and sensitive parameter for early cardiotoxicity detection. In a cross-sectional study, Ho et al [11] found that compared with normal volunteers, subclinical systolic myocardial abnormalities were present in asymptomatic breast cancer survivors up to 6 years after anthracycline treatment using speckle tracking echocardiography, which was proved by other speckle tracking echocardiography-derived study [12]. However, there was a limited study demonstrating early subclinical cardiotoxicity in patients receiving anthracycline.…”
Section: Beforementioning
confidence: 99%
See 1 more Smart Citation
“…The period of subclinical cardiotoxicity is characterized by structural and functional myocardial abnormalities and is highly prevalent amongst asymptomatic pediatric cancer survivors [21,[24][25][26][27][28]. Treatment of subclinical dysfunction with Enalapril and possibly Carvedilol may help prevent or decrease the incidence of cardiac events if started earlier after chemotherapy [29,30] and in addition may decrease cancer progression and cancer specific mortality in some patients [31].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, four studies evaluated the deformation parameters in long-term cancer survivors (range, 2-30 years after treatment). 150,154,163,164 In two of the studies with longer follow-up and/ or higher doses of anthracyclines, the LVEF (or fractional shortening) was slightly decreased. 163,164 In contrast, all four studies detected decreases in longitudinal and radial (and circumferential when studied) parameters compared with age-matched control patients, underlining the sensitivity of these parameters in the detection of sub-clinical LV dysfunction.…”
Section: Detection Of Sub-clinical LV Dysfunction Using Dti Velocitiesmentioning
confidence: 99%